Impact of pneumococcal conjugate vaccines on childhood otitis media in the United Kingdom. Issue 39 (22nd September 2015) - Lau, Wallis C.Y.; Murray, Macey; El-Turki, Aisha; Saxena, Sonia; Ladhani, Shamez; Long, Paul; Sharland, Mike; Wong, Ian C.K.; Hsia, Yingfen
Abstract Background Studies have demonstrated a reduction for otitis media (OM) following the introduction of seven-valent pneumococcal conjugate vaccine (PCV7), but this has not been evaluated in the United Kingdom (UK). Moreover, there are limited data on any additional impact of PCV13 introduction in 2010. Methods We conducted an observational cohort study to investigate the trends in OM incidence and associated antibiotic prescriptions in children aged <10 year-olds during 2002–2012 using a national primary care database. Three time-periods were defined to estimate monthly incidence: pre-PCV7 (January 2002–August 2006), post-PCV7 (September 2007–March 2010), and post-PCV13 (April 2011–December 2012). Results Overall annual OM incidence declined by 51.3% from 135.8 episodes/1000 person-years in 2002 to 66.1 episodes/1000 person-years in 2012; antibiotic prescription rates for OM declined by 72.9% from 57.9 prescriptions/1000 person-years to 15.7 prescriptions/1000 person-years, respectively. PCV7 introduction was associated with significant decline in OM rates across all age-groups (21.8%; 95% CI, 20.2–23.4), including <2 year-olds (19.8%; 95% CI, 16.0–23.5%); 2–4 year-olds (23.0%; 95% CI, 20.4–25.4%) and 5–9 year-olds (20.2%; 95% CI, 17.6–22.7%). There was an additional significant reduction in OM (18.5%; 95% CI, 16.7–20.2%) and associated antibiotic prescribing (12.2%; 95% CI, 8.6–15.6%) after the introduction of PCV13 across all age-groups. Conclusion The introduction of PCV7 was associated with a 22% significant reductions in OM in children aged <10 year-olds with an additional 19% reductions after PCV13 introduction. These declines are equivalent to 592, 000 and 15, 700 fewer consultations and OM-related hospitalizations, respectively, in England and Wales every year. Although the continuing decline in OM rates in our study suggests that further reduction may continue to occur, it is important to monitor long-term trends in all pneumococcal diseases, including OM and pneumonia, because of increasing replacement of non-vaccine pneumococcal serotypes in carriage and disease.